Comprehensive growth and nutritional study of Azolla filiculoides Lam. as source of fiber and protein for ruminant’s diet - Hamidan, Mohammad Fitri Rimi (2023)
Constraints in Napier grass production such as limited land use, labor shortages and long cutting intervals had become the factors that cause the underdeveloped situation on the ruminant industry. As an alternative, the use of water fern species known as mosquito fern (Azolla filiculoides Lam.) as a source of fiber and protein in livestock diets is seen as suitable due to its adequate composition of crude protein and crude fiber that required by ruminants which are in the range of 19-25% DM-1 and 12-18% DM-1 respectively. Furthermore, this species is very practical and economical to be self-produced by the farmers in their farms. This study was carried out to determine the potential of A. filiculoides as an alternative feedstuff in ruminant diet. An objective of Study 1 was to evaluate the potential of different fertilizer (NPK 15:15:15, broiler manure, sheep manure and cow manure) with increasing concentrations of 0.25 g/L (C1), 0.50 g/L (C2), 0.75 g/L (C3), 1.00 g/L (C4) and 1.25 g/L (C5) on growth and nutritive value of Azolla filiculoides. Objective of study 2 was to determine the practical procedures between dried (T1), burned (T2) and freshly used (unprocessed) (T3) in preparing a livestock manure according to an optimum concentration for A.filiculoides cultivation based from the finding of the first study. Study 3 was conducted to analyze the effectiveness of Azolla meal as an inclusion of 0% (control), 6% (TMR 1), 10% (TMR 2), 17% (TMR 3) and 23% (TMR 4) inclusion in the Napier silage TMR based on digestibility and VFA profile. All experiment was designed according to Complete Randomized Design (CRD) with four replication each. The analysis was carried out according to the method that had been developed in AOAC and the data was analyzed using two or one-way ANOVA according to the factors tested and significant differences were determined through Duncan's Multiple Range Test (DMRT). As a result, sheep manure was able to produce a higher fresh weight (136 g m-2). In fact, the application of C4 (1.00 g/L) sheep manure in the Azolla filiculoides cultivation was able to produce dry matter: 7.3% kg DM-1, ash: 19.6% kg DM-1, crude protein: 21.2% kg DM-1, ether extract: 4.3% kg DM-1 and crude fiber: 14.4% kg DM-1. Subsequently, the application of T3 procedure for A.filiculoides cultivation was able to produce higher yields (p<0.05) with lower fiber components (NDF: 33.02% kg DM-1, ADF: % kg DM-1 and ADL: 8.13% kg DM- 1) compared to the application of T2 procedure for manure preparation. The value of IVDMD and IVOMD as 82.9% and 43.7% proved that digestibility increased by using Azolla meals in the ruminant dietary feed. Although the IVDMD and IVOMD were decrease with increment of the inclusion, Azolla meal could supply 14.1 MJ/kg ME at 6% inclusion in the ruminant diet. To conclude, A. filiculoides at 6% inclusion has show a potential as a practical and economic source of fiber and protein by direct cultivation in the farm employing sheep manure (T3) at 1.00 g/L concentration (C4).